Facies Analysis and Sandbody Geometry of the Paleogene Battfjellet Formation, Central Western Nordenskiöld Land, Spitsbergen - Gjelberg, Helge Kollsete (The University of Bergen, 2010)
New sedimentological data from the central part of Nordenskiöld Land, Spitsbergen, contributes to the understanding of the depositional processes and sandbody geometry of the Battfjellet Formation (Eocene). A detailed study, with focus on internal facies distribution and local parasequence stacking pattern, has been carried out in an approximately 70km2 study area. A total of twelve aggrading and forwards stepping parasequences of a fluvio-wave dominated deltaic origin are recognized. Local variations and complex geometry of the parasequences in the formation are best explained by autogenic mechanisms and accompanied delta lobe switching, characteristic of a delta with a fluvial dominated morphology (Helland-Hansen, 2010). In contrast, facies analysis of the formation reveals a predominance of wave generated structures. However, the parasequences locally show a characteristic development of alternating plane parallel laminated sandstone units (5-30 cm set thickness) and symmetrical small scale ripples. These units reflect deposition in front of, or close to, an active river mouth bar system, strongly influenced by hyperpycnal flow processes during flood events and accompanying wave reworking during waning flood and fair weather aggradation. The local variations of this facies makes it possible to recognize and map the position of the most fluvial influenced shoreface/delta front successions and their spatial distribution as a consequence of auto-cyclic lobe change processes. In contrast to the well studied western, more proximal positioned, reaches of the basin, there are no developed clinothems or basin floor fan systems in the study area. This has been interpreted to be a consequence of the progressive shallowing of the basin through time. Master i Geovitenskap MAMN-GEOV GEOL399